RNS-based implementation of 2-D discrete wavelet transform - Liu, Yong (2008)
This thesis describes the design and implementation of a residue number system (RNS) based two-dimensional (2-D) discrete wavelet transform processor using Daubechies biorthogonal 9/7-tap filter bank with symmetric extension.